SOSIALILISASI PEMBUATAN STUP SEBAGAI UPAYA MENINGKATKAN PRODUKSI HASIL HUTAN BUKAN KAYU (HHBK) MADU TRIGONA SP - Siruru, Herman; Lamerkabel, Jacobus Suruka Aifaman; Tan, Lieke; Liliefna, Leonard Dantje; Fransz, Jimmy Johanson; Titarsole, Jimmy; Maail, Rohny Setiawan; Parera, Lydia Riekie; Mustamu, Sofia; Imlabla, Wilma Nancy Imlabla Nancy (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Manusela National Park borders several villages to the south. The proximity of the village location to the National Park is an opportunity to improve the family economy based on Non-Timber Forest Products (NTFPs) through cultivating Trigona sp bees. The aim of Community Service activities is to educate and train the community of bee farming groups to provide stock. Community Service Activities were carried out in collaboration with the Manusela National Park Office, in Moso village, Central Maluku Regency on 21-25 November 2023. The communities who are stakeholders in this activity are honey farmer groups from 3 villages, namely: Moso village, Teluti Baru and Hattu. PKM activity participants are involved in all series of activities starting from delivering materials for making stups to placing stups. The resulting stup was 10 units and 3 units were placed in each village and 1 stup unit was placed around the location where the stup was made.